EFFICIENCY EVALUATION OF BUSINESS EDUCATION ACCORDING TO EXPERTS FROM VARIOUS COUNTRIES - Pinkovetskaia, Iuliia; Lebedev, Anton; Shamina, Natalya; Tsybina, Larisa (Revista Inclusiones, 2020)
The aim of the study is to evaluate business education in 54 countries according to local experts. The study is based on the Global Entrepreneurship Monitoring for 2018. The models were developed that describe the indicators of effectiveness of school children, students, and adults’ professional and higher education. The density functions of the normal distribution are used as models. The results of the study allowed to determine the average values and intervals of change for most countries of the indicators values describing the experts’ opinion on a ten-point scale.